Knowledge sharing: Role of academics towards research productivity in higher learning institution - Muhammad Ashraf, Fauzi; Christine Tan, Nya-Ling; Ramayah, Thursamy; Ojo, Adedapo Oluwaseyi (Emerald Publishing, 2019)
Purpose – Academics research productivity is the pinnacle issue of higher learning institution (HLI) quest for providing the best service for the community and a country’s as a whole. Being productive in their area of expertise will determine how far HLI can challenge for the best education in the world. In lieu of this, knowledge sharing (KS) behavior determinants are assessed to determine what factors that can contribute to academic’s research productivity. Design/methodology/approach – A quota sampling method was applied in selecting academics from public and private universities in Malaysia. A partial least square structural equation modelling (PLS-SEM) was used for analysis. Findings – The results show that academics productivity explained variance is 22.6 per cent. This suggests that academics KS behavior has substantial impact on research productivity. As for determinants of academic’s attitude, academics commitment, trust and social network constituted an explained variance of 36.4 per cent. Management support has an explained variance of 38.7 per cent towards subjective norm, while facilitating condition and socialmedia has an explained variance of 26.5 per cent towards perceived behavioral control (PBC). Academics KS intention and KS behavior explained variance were 62.1 and 47.1 per cent, respectively. Research limitations/implications – All the hypotheses result in significant relationship except for H1, commitment toward attitude. The impact of this study will be discussed in term of its theoretical and managerial perspectives. Originality/value – The KS behavior in a multiracial and multinational country in Malaysia can be a benchmark for Asian countries in general.